Penerapan Pemodelan Spasial pada Sistem Informasi Geografis Tenaga Kesehatan Kabupaten Malang - Auliasari, Karina; -, Sukmadiningtyas (MATICS, 2016)
Abstract—Geographic information systems can improve the health services to the community. This system able to provide spatial considerations in determining the type of health services and accessibility to public health facilities.The increase of health care needs, especially in Kabupaten Malang still has an unbalanced ratio between health-care facilities and service needs, so that the necessary to improve the facility and medical personnel. In this research is to developed a geographic information system that provide the visualization. The visualization of the mapping is visualization the distribution of medical personnel in Kabupaten Malang. The system generates mapping visualization that equipped with a comparative analysis of the number of medical personnel and the population of Kabupaten Malang. In this system also provides a potential data of health facilities in Kabupaten Malang. The system is also supported with data management to change facilities and medical personnel data. Results from the mapping showed that the health personnel, particularly physicians uneven. Nine of a total of thirty-three districts in Malang has a number of doctors that excessive when compared with the rest of the other districts are still lacking.